Determinants of Districts Poverty in West Java in 2016-2019 - Muthia Amanatunnisa; Imamudin Yuliadi (Journal of Asset Management and Public Economy (JAMPE), 2022)
Poverty is a major problem faced by all countries. Poverty can be defined as a condition when a person or group of people do not have the capability to fulfill their basic rights to maintain and develop a dignified life. This study was aimed to determine the effect of Human Development Index (HDI), Regional Gross Domestic Product (RGDP), Open Unemployment Rate (TPT), Total Population, School Enrollment Rate, and Food Consumer Price on Poverty in Indonesia in 2016 - 2019 using case studies from 17 districts in West Java and was done by analyzing panel data regression using Eviews 10. Panel data is a method combining time data and cross data. The results indicated that Human Development Index, Population, and Food Consumer Prices have a significant effect on Poverty in districts in West Java with the probability value less than 0,05, while the Open Unemployment Rate, Regional Gross Domestic Product, and School Enrolment Rates have no significant effect on district poverty in West Java with the probability value more than 0,05.